The contribution of the flight phase in elite race walking - Hanley, B.; Bissas, A.; Drake, A. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Although race walkers are not permitted a visible flight phase, previous research has found that most competitors do experience very brief losses of contact. The purpose of this study was to assess the role of the flight phase in elite race walking. Seventeen international athletes race walked over two force plates recording at 1000 Hz. Video data were simultaneously recorded at 100 Hz and used to calculate kinematic variables such as step length. The mean flight time was 0.030 s (± .011) while the mean distance travelled during this phase was 0.12 m (± .05). It was calculated that without flight times, athletes would have slower mean velocities, particularly if mean cadence remained the same. However, the contribution of flight phases in race walking does not just allow for greater step lengths and faster speeds, but also more time for lower limb repositioning.